2018
DOI: 10.5455/ajpmph.20170927084148
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of pulmonary impairment among diverse working groups in coal mine

Abstract: Aim:There are different categories of workers depending upon their involvement in mining operation who are exposed to different levels of dust and for different durations. The occurrence and degree pulmonary impairment may differ among different workers in the same mining environment. The aim of the study was to evaluate and compare the respiratory function parameters of actively engaged exposed mine workers to that of supportive workers with respect to their duration of work exposure. Methods: 207 workers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The study found that the control group's respiratory function was significantly better than that of the study group, although in the study group the mean number of years of smoking was shorter than in the control group (32). These results are consistent with recent epidemiological studies that study the relationship between decreased lung function status in workers on the effects of tobacco smoke and exposure to coal dust (73).…”
Section: Smoking Statussupporting
confidence: 85%
“…The study found that the control group's respiratory function was significantly better than that of the study group, although in the study group the mean number of years of smoking was shorter than in the control group (32). These results are consistent with recent epidemiological studies that study the relationship between decreased lung function status in workers on the effects of tobacco smoke and exposure to coal dust (73).…”
Section: Smoking Statussupporting
confidence: 85%
“…There are addictive substances in cigarettes that can damage human respiratory organs, especially the lungs, which can cause damage to function and tissue structure in the lungs. 15 Secondhand smoke is smoke from active smokers inhaled unconsciously by passive smokers. 22 Cigarette smoke contains more than 7,000 chemicals in it.…”
Section: Discussionmentioning
confidence: 99%
“…14 Cigarette smoke exposure is a risk factor for decreased lung function status, causing health risks. 15 The effect of smoke exposure affects the functional lung capacity of workers. Finding cafes or restaurants indoors and outdoors in Pontianak City is not difficult; they are spread along the roads.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is one of the risk factors in decreasing lung function status cause of health risks and the emergence of respiratory and cardiovascular diseases (29). Smoking can also damage the alveoli in a person's lungs.…”
Section: Smoking Habitmentioning
confidence: 99%
“…The combination of exposure to coal dust and smoking can worsen a person's lung condition. Several epidemiological studies studying the association of coal dust exposure with tobacco smoke's effect on workers' lung status have shown decreased lung function (29).…”
Section: Smoking Habitmentioning
confidence: 99%